2018
DOI: 10.1080/14728222.2018.1498082
|View full text |Cite
|
Sign up to set email alerts
|

The potential utility of PFKFB3 as a therapeutic target

Abstract: It has been known for over half a century that tumors exhibit an increased demand for nutrients to fuel their rapid proliferation. Interest in targeting cancer metabolism to treat the disease has been renewed in recent years with the discovery that many cancer-related pathways have a profound effect on metabolism. Considering the recent increase in our understanding of cancer metabolism and the enzymes and pathways involved, the question arises as to whether metabolism is cancer's Achilles heel. Areas covered:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 127 publications
1
53
0
Order By: Relevance
“…PFKFB3 is a bifunctional enzyme that catalyzes the synthesis and the degradation of fructose‐2,6‐bisphosphate. PFKFB3 is recognized as a key metabolic driver in cancer cells, and the molecule is considered a therapeutic target to inhibit cell proliferation and impair survival . CD4 T cells from healthy individuals upregulate PFKFB3 upon stimulation, with a maximum expression 72 h poststimulation.…”
Section: Ra Cd4 T Cells Shunt Glucose Toward the Pentose Phosphate Pamentioning
confidence: 99%
See 1 more Smart Citation
“…PFKFB3 is a bifunctional enzyme that catalyzes the synthesis and the degradation of fructose‐2,6‐bisphosphate. PFKFB3 is recognized as a key metabolic driver in cancer cells, and the molecule is considered a therapeutic target to inhibit cell proliferation and impair survival . CD4 T cells from healthy individuals upregulate PFKFB3 upon stimulation, with a maximum expression 72 h poststimulation.…”
Section: Ra Cd4 T Cells Shunt Glucose Toward the Pentose Phosphate Pamentioning
confidence: 99%
“…PFKFB3 is recognized as a key metabolic driver in cancer cells, and the molecule is considered a therapeutic target to inhibit cell proliferation and impair survival. 19,20 CD4 T cells from…”
Section: R a CD 4 T Cell S S H Unt G Lucos E Toward The Pentos E Phmentioning
confidence: 99%
“…Among all PFKFBs, PFKFB3 exerts a central role in controlling glycolysis flux and has aroused a great deal of attention in recent years . In addition to activation of mTORC1, inactivated mutation of Pten or the aberrant activation of Ras and PI3K have been shown that take part in the regulation of glycolysis and tumorigenesis through modification of PFKFB3 expression . However, the detailed transcriptional regulation mechanisms of PFKFB3 expression are far from fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…34 In addition to activation of mTORC1, inactivated mutation of Pten or the aberrant activation of Ras and PI3K have been shown that take part in the regulation of glycolysis and tumorigenesis through modification of PFKFB3 expression. 35,36 However, the detailed transcriptional regulation mechanisms of PFKFB3 expression are far from fully understood. Zhu et al demonstrated that the transcription factor PU.1 upregulates PFKFB3 which is responsible for the chemoresistance in chronic myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“… 4 The activity of PFK-1 is under the control of F2,6P2, which is generated by the phosphorylation of F6P to fructose-2,6-bisphosphate (F2,6BP). 5 This reaction is catalyzed by enzymes in the 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase family. One member, PFKFB3, has been shown to be upregulated in various cancers and associated with poor survival in patients with cancer, including breast cancer, gastric cancer, colorectal cancer, and glioblastoma.…”
Section: Introductionmentioning
confidence: 99%